Aortic rupture following an EVAR secondary to graft erosion. Issue 4 (28th October 2015) - Banzic, Igor; Lachat, Mario; Rancic, Zoran
Abstract : Significant type 3 endoleak as a defect in the graft material, especially associated with endograft rupture, is a rare complication. A 68‐year‐old male patient with aortic plaque rupture was treated with endovascular graft placement. The patient was readmitted two years later with severe abdominal pain, a large retroperitoneal hematoma and contrast extravasation below the location where the aortic plaque had presented. Before an aortic infrarenal cuff could be placed during a control angiography, a large graft hole and a significant type 3 endoleak were observed. The sharp aortic plaque may have been responsible for the endograft tear. © 2015 Wiley Periodicals, Inc.